Pemaknaan Tata Ruang Interior Museum Kebangkitan Nasional Jakarta - Ika Yuni Purnama (Fakultas Seni Rupa - Institut Kesenian Jakarta, 2021)
Abstrak: Secara umum bangunan Museum Kebangkitan Nasional masih mencerminkan suasana sekolah kedokteran STOVIA. Sekolah STOVIA, Sekolah Dokter Jawa menandai era ilmu kesehatan, dari penyembuhan berbasis tradisi ke arah pengobatan modern. Museum ini, tidak dapat dipisahkan dari sejarah pendidikan kedokteran di Indonesia dan sejarah Rumah Sakit Militer (sekarang R.S. Gatot Subroto), Sekolah Kedokteran di Salemba dan Rumah Sakit Cipto Mangunkusumo. Selain itu juga berbagai gerakan yang mengerucut menjadi gerakan kebangsaan dan kemerdekaan di tahun 1928 dan 1945 dengan pemicu Boedi Oetomo. Dari hasil observasi langsung, ketiga konteks tersebut pada Museum Kebangkitan Nasional dipaparkan dengan jelas melalui pengaturan tata ruang interior yang terbagi dan terorganisir dengan baik. Terdapat berbagai ruang peragaan yang mewakili setiap cerita bersejarah terkait sejarah kebangkitan nasional Indonesia. Tujuan penelitian ini adalah untuk mendapatkan data tentang bentuk tata ruang interior dan pemaknaan sejarah pendidikan khususnya bidang kedokteran di Indonesia sehingga menambah pengetahuan mengenai desain interior museum, khususnya Museum Kebangkitan Nasional sebagai wahana pelestarian warisan budaya sejarah bangsa. Abstract: In general, the National Awakening Museum building still reflects the atmosphere of the STOVIA medical school. The establishment of the STOVIA School, the Javanese Medical School which marks the era of health science, from tradition-based healing to modern medicine. This museum, can not be separated from the history of medical education in Indonesia and the history of the Military Hospital (now R.S. Gatot Subroto), the Medical School in Salemba and Cipto Mangunkusumo Hospital. Besides, various movements that narrowed to become a nationalism and independence movement in 1928 and 1945 with trigger Boedi Oetomo. From direct observation, the three contexts at the National Awakening Museum are clearly explained through their well-organized and well-organized interior spatial arrangements. There are a variety of demonstration spaces that represent each historical story related to the history of Indonesia's national revival. The purpose of this study was to obtain data on the form of interior spatial planning and the meaning of educational history, especially in the field of medicine in Indonesia, to increase knowledge about the museum's interior design, specifically the National Awakening Museum as a vehicle for preserving the nation's cultural heritage.